2000
DOI: 10.1161/01.cir.102.4.464
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Slow Conduction Zone During Reentrant Ventricular Tachycardia

Abstract: Background-Reentrant ventricular tachycardia is sometimes difficult to treat effectively because localizing the slow conduction zone (SCZ) for catheter ablation may be problematic. It was hypothesized that a linear relationship exists between activating wave-front acceleration and deceleration in the SCZ and, respectively, contractions and expansions of the far-field extracellular signal, which could be used for SCZ localization. Methods and Results-To test the hypothesis, a model was developed to approximate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…19 In terms of determining conduction velocity, the limitation of this study is that we defined conduction velocity as the time from the pacing spike to the MAP onset between the center of LV anterior wall and apex, although recent mapping analysis can determine it accurately. 20,21 In this study, we found that conduction velocity diminished at 13W and 16W, though it was not reduced at 10W. Previous studies have shown that conduction velocity is somewhat enhanced early in the hypertrophic process, 6 and that this is related to decreased intercellular junctional impedance and enhanced connexin expression.…”
Section: Discussionsupporting
confidence: 47%
“…19 In terms of determining conduction velocity, the limitation of this study is that we defined conduction velocity as the time from the pacing spike to the MAP onset between the center of LV anterior wall and apex, although recent mapping analysis can determine it accurately. 20,21 In this study, we found that conduction velocity diminished at 13W and 16W, though it was not reduced at 10W. Previous studies have shown that conduction velocity is somewhat enhanced early in the hypertrophic process, 6 and that this is related to decreased intercellular junctional impedance and enhanced connexin expression.…”
Section: Discussionsupporting
confidence: 47%
“…1,2,8,19 Mapping studies performed on intraoperative patients 20 and explanted hearts 21,22 and during catheter mapping [3][4][5][6][7] indicate that although tissue excitability and the cellular action potential may be normal in the infarcted human heart, 23 regions of myocardium forming the diastolic pathway have abnormal conduction properties, but these studies lack the resolution to show which regions of the circuit are responsible for the greatest slowing of conduction. Although anisoptropy, 19 wavefront turning, 10,13 and other factors have been shown to affect conduction in animal studies, which of these factors predominate in causing slowing of conduction in human VT remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Mapping studies of the infarcted human left ventricle (LV) have confirmed that ventricular tachycardia (VT) is dependent on slowing of conduction through a discrete, largely endocardial diastolic pathway bordered by lines of conduction block [3][4][5][6][7] ; the precise location and mechanism of conduction slowing within the diastolic pathway are unknown. Slow conduction is necessary to maintain reentry 8 but also occurs in regions prone to conduction block. 9 Understanding the mechanisms of slow conduction in human VT will assist in recognition and localization of regions of circuits most prone to conduction block and termination of tachycardia.…”
mentioning
confidence: 99%
“…5,7,8,[12][13][14] At convergence to the optimal weighting, the final weighting is a quantitative measure of the degree of similarity between the two signals. APM has been shown to be useful in cardiovascular research for prediction of the location of reentrant ventricular tachycardia 7,8,[12][13][14] and for region-finding in biomedical magnetic resonance images. 5 In fact, ANC can be considered to be a special case of APM in which the pattern (reference signal) is matched to the input (desired signal) discrete point by discrete point for an indefinite interval.…”
Section: Convergence To the Optimal Weightingmentioning
confidence: 99%